Early and mid-term outcomes of mitral annular calcification and transcatheter mitral therapy: a systematic review - Sakurai, Yosuke; McDonald, Ashton; Kaneko, Tsuyoshi (Annals of Cardiothoracic Surgery, 2025)
Background: Mitral annular calcification (MAC) poses technical and clinical challenges in patients undergoing mitral valve intervention. Patients with severe MAC were excluded from major previous randomized controlled trials evaluating mitral therapies. Consequently, outcomes following mitral transcatheter edge-to-edge repair (M-TEER) in this population remain controversial. Methods: MEDLINE and EMBASE were searched through June 2025 to identify studies reporting outcomes after M-TEER in patients with MAC. This systematic review assessed the difference in MAC grading and M-TEER eligibility across studies. The definition of procedural success was documented to highlight inconsistencies. The primary endpoint was all-cause mortality during follow-up. Secondary endpoints included procedural success, heart failure rehospitalization, mitral valve reintervention, residual mitral regurgitation (MR), and mean mitral gradient. Results: Six studies met inclusion criteria, including 2,808 patients undergoing M-TEER, of whom 363 (12.9%) had moderate-to-severe MAC. Most studies defined procedural success as MR reduction to grade ≤2, though only one incorporated a mean transmitral gradient